Effectiveness of 6% hydrogen peroxide concentration for tooth bleaching-A double-blind, randomized clinical trial - Martín, J. [UNESP]; Vildósola, P. [UNESP]; Bersezio, C. [UNESP]; Herrera, A.; Bortolatto, J. [UNESP]; Saad, J. R. C. [UNESP]; Oliveira, O. B. [UNESP]; Fernández, E. [UNESP] (Elsevier B. V., 2015)
The aim of this clinical randomized double-blind split-mouth study was to assess the effectiveness of a 6% hydrogen peroxide with nitrogen-doped titanium dioxide light activated bleaching agent. 31 patients were treated with: one upper hemiarcade with a 35% hydrogen peroxide bleaching agent and the other hemiarcade with a 6% hydrogen peroxide. Two applications were completed each treatment session and three sessions were appointed, with one week interval between them. Tooth colour was registered each session and 1 week and 1 months after completing the treatment by spectrophotometer, registering parameters L*, a* and b*, and subjectively using VITA Classic guide. Tooth sensitivity was registered by VAS and patient satisfaction and self-perception result was determined using OHIP-14. Tooth colour variation and sensitivity were compared between both bleaching agents. Both treatment showed a change between baseline colour and all check-points with a ΔE=5.57 for 6% and of ΔE=7.98 for the 35% one month after completing the (p<0.05). No statistical differences were seen when subjective evaluations were compared. Also, no differences were seen in tooth sensitivity between bleaching agents. OHIP-14 questionnaire demonstrated a significant change for all patients after bleaching. A 6% hydrogen peroxide with nitrogen-doped titanium dioxide light activated agent is effective for tooth bleaching, reaching a ΔE of 5.57 one month after completing the treatment, with no clinical differences to a 35% agent neither in colour change or in tooth sensitivity. A low concentration hydrogen peroxide bleaching agent may reach good clinical results with less adverse effects.
Keywords: Bleaching teeth; Clinical randomized trial; Effectiveness; Low concentration; Ohip-14; Titanium dioxide